Sustainability Transformation: Leadership, Innovation, and Strategic Flexibility Improve Sustainability Performance - Hidayat, Rahmat; Komarudin; Wibowo, Setyo F.; Sorongan, Fangky A. (Ital Publication, 2025)
This study investigates how sustainability leadership impacts sustainability performance through strategic flexibility and sustainability innovation, which function as the mediators. This study collected data from 200 respondents using purposive sampling and 6-point Likert scale questionnaires. The data were subsequently analyzed using PLS-SEM. The findings confirm that sustainability leadership significantly and positively impacts sustainability performance through strategic flexibility and innovation. Additionally, data analysis revealed that sustainability leadership has a positive and significant impact on strategic flexibility and sustainability innovation. This study highlights the unique aspect of the Indonesian mining sector. It has not received extensive examination regarding sustainability and sustainability leadership as systems thinking that requires the perspective of interdependent structures and adaptability to changes. Strategic flexibility, as an organization's capability to adapt to changes reactively and proactively, is crucial to the organization's effort to create sustainability innovation to ensure sustainability performance.